Convergence of the Galerkin method for a wave equation with singular right-hand side - Nomirovs'kii, D. A. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We consider analogs of the Galerkin method for a linear wave equation of the fifth order with generalized functions on the right-hand side. Theorems on the convergence of an approximate method, depending on the order of singularity of the right-hand side, are proved.